Unilateral Exoskeleton Imposes Significantly Different Hemispherical Effect in Parietooccipital Region, but Not in Other Regions - Li, Junhua (Sci Rep, 2018)
In modern society, increasing people suffering from locomotor disabilities need an assistive exoskeleton to help them improve or restore ambulation. When walking is assisted by an exoskeleton, brain activities are altered as the closed-loop between brain and lower limbs is affected by the exoskeleton. Intuitively, a unilateral exoskeleton imposes differential effect on brain hemispheres (i.e., hemispherical effect) according to contralateral control mechanism. However, it is unclear whether hemispherical effect appears in whole hemisphere or particular region. To this end, we explored hemispherical effect on different brain regions using EEG data collected from 30 healthy participants during overground walking. The results showed that hemispherical effect was significantly different between regions when a unilateral exoskeleton was employed for walking assistance and no significance was observed for walking without the exoskeleton. Post-hoc t-test analysis revealed that hemispherical effect in the parietooccipital region significantly differed from other regions. In the parietooccipital region, a greater hemispherical effect was observed in beta band for exoskeleton-assisted walking compared to walking without exoskeleton, which was also found in the source analysis. These findings deepen the understanding of hemispherical effect of unilateral exoskeleton on brain and could aid the development of more efficient and suitable exoskeleton for walking assistance.